Territórios africanos: colonização ímpia, descolonização cruel e globalização perversa - Romualdo Pessoa Campos Filho; Natália Müller de Deus; Maria Angélica de Sousa Santos (Confins)
One of the greatest challenges for Geopolitics today is to understand the contradictions that plague Africa and its social consequences. The conflicts that lead the African population to the need to flee their countries of origin to live in refugee camps are the result of historical processes that have profoundly marked the development and security conditions in African states. In order to understand and analyze the conflicts that are present in Africa today, we seek through historical research to understand the main processes that placed Africa and its population in an environment of permanent crisis: colonization, decolonization and globalization. Understanding the perversity of these processes for the African continent is fundamental in understanding the reality and recent events in Africa, fruits of imperialist domination and economic interests in the natural resources available on the continent.